Humanitarian Dalam Penerapan Hukum Ekonomi Syari’ah - Muhammad Hasan (Khatulistiwa, 2016)
Humanitarianism in Islamic economic law is interesting to study because as stated by Chaprah that the objectives and functions of monetary and banking systems have some similarities with those in the capitalist system. However, despite many similarities, there are significant differences in emphasis due to divergences in the commitment to spiritual values, social and economic justice, and human brotherhood. In Islamic economic law, production, distribution, and consumption are not only limited by the horizontal rights, but is also limited by the vertical rights. Humanitarianism in Islamic economic law is attached to the egalitarianism, justice and humanity. Egalitarianism is a concept that is needed in modern society, in which the tendency of modern society is individuality. Justice and humanity basically is something that is aspired by modern society but difficult to realize.